(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Upper Jurassic strata of the Larsen Basin, in the northeastern tip of the Antarctic Peninsula (Fig. 1), consist of thin, well-bedded, radiolarian-rich shales, fallout tuffs and volcaniclastic sandstones, grouped in a stratigraphic unit known as Ameghino Formation (or Nordenskjöld Formation for British authors - see Whitham and Doyle, 1989). The Ameghino Formation succession records a fine-grained and high-rate continuous suspensive sedimentation in a quiet hemipelagic environment, with little reworking at the bottom. A 1.3 m-thick representative section for the Upper Member of the Ameghino Formation was sampled bed by bed and studied under petrographic microscopy for microfacies determination. Cyclicity was defined by means of Markov chain analysis and Fourier series (Blackman- Tukey and wavelet methods). Microfacies: The succession is composed of a microfacies association of radiolarian-rich shales (P1), black shales (P2), bioturbated and peloidal shales (P3), tuffs (T) and sandstones (A) superbly preserved (Figs. 2 and 3). Sedimentation took place in an oxygen-depleted environment, periodically interrupted by rapid, event-sedimentation mostly caused by large explosive eruptions at the volcanic arc of the Antarctic Peninsula. The P1 and P2 microfacies are interpreted as the result of the deposition from pelagic suspensions during cycles of varying biological productivity or terrigenous dilution. The microfacies P3 represents similar conditions of sedimentation but higher oxygenation levels at the bottoms. On the other hand, microfacies T and A correspond to fallout deposits and distal turbiditic flows respectively. Microfacies T is associated with siliciclastic explosive volcanic eruptions and microfacies A with reworking of primary pyroclastic deposits. Markov chain and Fourier series analysis: Markov chain analysis reveal cyclic relations between some microfacies with single step transition dependence (Figs. 4 and 5). Transition diagram shows statistically significant transitions from microfacies T and A to P1, between P1 and P2, and also a cycle T-P1-P2 (Fig. 6). Spectra from the Fourier series analysis on 37 pairs P1-P2 (Fig. 7 a) indicate a periodicity of 1140 years (Blackman-Tukey method, 95% confidence, Fig. 7b), and periodicities of 740 and 1160 years (wavelet method, Fig. 7c). Ages were derived from sedimentation rates calculated by Scasso (2001) for the Longing Member due to poor age determinations in the upper Member. A periodicity of about 1000 years may be associated with the Hallstatt cycle of solar activity that influence the intensity of solar radiation reaching the Earth and cause surface temperature variations within the sub-Milankovitch frequency band. A similar frequency was calculated by Scasso (2001) for large volcanic eruptions from the tuff record in the Longing Member. Therefore, P1- P2 transitions are associated to climatic cycles that influence productivity at the surface of the oceans. The accumulation of microfacies T and A are related to events of siliciclastic sedimentation that modified environmental and early-diagenetic conditions avoiding dissolution of radiolarian skeletons in the water body and at the bottom and caused the T and A transitions to P1. P2-T transition might indicate that P2 environmental conditions lasted longer than P1 conditions in spite of the similar thickness observed for both microfacies.